The Training Curriculum is Based on the Problem Solving and Decision Making Blended Learning to Improve the Employees’ Soft Skills - Tris Sutrisno; Laksmi Dewi (JURNAL APARATUR, 2022)
The objective of this study is to develop a training curriculum design based on the problem solving & decision-making blended learning to improve the employees’ soft skills. The specific objectives of this study are 1) to determine the need for Problem Solving & Decision-Making competencies based on the results of training needs analysis; 2) to determine the training curriculum design based on the problem solving & decision-making blended learning to improve employees’ soft skills; and 3) to determine the result of expert judgments in relation to the training curriculum design. The study uses a design and development research approach and curriculum validation of expert judgment. The results of this study are as follows: 1) based on the training needs analysis, the data gathered shows that the employees’ current competency in solving problems and decision-making is not in accordance with the current Problem Solving & Decision-Making training program. 2) The parts developed in the Problem Solving & Decision-Making curriculum include the structure of curriculum components covering the training objective, training material, training hours, learning process both on the methods and media used, and evaluation on the program. 3) Based on the results of expert judgements on the training curriculum on aspects of objectives, material, process, and evaluation, the average assessment result is "Good".